Aerodynamic simulation and adjoint-based optimisation of rotorcraft configurations - Zhang, T.; Barakos, G.N. (My University, 2021)
This paper presents high-fidelity, as well as, simplified CFD modelling approaches within an optimisation framework for compound rotorcraft configurations with rotor/propeller aerodynamic interactions. The actuator disk/line models are used to represent the main rotor for simulations of a generalised rotor/propeller combination. The propeller performance is analysed in detail, and large variations are observed in the single blade loading due to the main rotor wake. A simplified model for the rotor/propeller interaction simulation is also put forward, and an inflow distortion metric is proposed to quantify the aerodynamic interactions. With the help of a Kriging surrogate model and the inflow distortion metric, aerodynamic interferences through the propeller disk are quantitatively visualised with variations in the propeller position, propeller thrust, and main rotor advance ratio. Optimisation of the propeller position under the main rotor for minimised interference with rolling/pitching moment constraints are also attempted using both gradient-based (adjoint) and gradient-free (efficient global optimisation) approaches. The optimisation results are validated using blade resolved simulations, and fluctuations of the propeller single blade loading were effectively reduced due to the optimisation. The work is a first step towards high-fidelity methods for vehicle and configuration optimisation.